Representation of Environmental Awareness in the Song Plastic Tree: A Semiotic Study Based on Ferdinand de Saussure’s Theory - Ichsa Janand, Handy; Santi, Diana; Rahayu, Rina (LPPM Universitas Dhyana Pura, 2025)
Environmental issues caused by plastic waste have become both an ecological and humanitarian crisis. In response to this reality, this study aimed to explore how the song Plastic Tree by Endah N Rhesa serves as an agent of ecological critique through poetic symbolism. Using Ferdinand de Saussure’s semiotic approach, the song lyrics were analysed as signs conveying hidden environmental meanings. Symbols such as “plastic tree,” “rubber bee,” and “paper bird” reflect the loss of natural ecosystems replaced by lifeless artificial objects. The analysis revealed that the song successfully builds ecological awareness and rejects superficial solutions, thereby encouraging listeners to become more reflective and concerned about their surrounding environment.